Effects of Dietary Clostridium butyricum on Growth and Intestinal Mucosal Barrier Functions of Juvenile Channel Catfish (Ictalurus punctatus) - Zihe Guo; Ye Qian; Xiao Peng; Chanxia Qin; Huige Ren; Jingyi Du; Chengrui Huang; Mingzhu Pan; Weihao Ou (Microorganisms)
An 8-week feeding trial was conducted to investigate the effects of dietary Clostridium butyricum on the growth and intestinal mucosal barrier functions of juvenile channel catfish (Ictalurus punctatus). The diets included the control group feed (CD group) and the treatment group feed (containing 1 × 108 CFU/g C. butyricum; CB group). The CB group showed a rising trend in the growth performance. The CB group had significantly higher digestive and antioxidant enzyme activities, and significantly lower malondialdehyde and superoxide anion contents of the intestine. In terms of intestinal mechanical barrier, the CB group showed significantly higher gene expression of intestinal tight junction proteins. With regard to intestinal immune barrier, the CB group displayed significantly lower gene expression of pro-inflammatory factors. Regarding intestinal chemical barrier, the CB group had significantly higher gene expression of mucin-4, β-galactoside-binding lectin, lysozyme-c, and NK-lysin type 1. Dietary C. butyricum significantly increased the abundance of some beneficial bacteria and increased the levels of some beneficial metabolites in the intestine. Collectively, dietary C. butyricum could increase growth, enhance intestinal digestion and antioxidant capacity, strengthen intestinal mucosal barrier, and improve the intestinal metabolism of juvenile channel catfish.